The Language of Praise Creation's Silence in Psalms 19 and 65 - Petrany, Catherine 1981- (2025)
Attention to the role of silence in the psalms often focuses on the experience of divine absence that generates laments (e.g., Pss 13:2-3; 22:2-3). Yet multiple silences populate the psalms, whether in the muted agony of the sufferer (Ps 38:14-15) or in the injunction to silent wisdom that awaits God's justice (Ps 37:7). In this article, I explore positive manifestations of silence in contexts of praise in Psalms 19 and 65. Both psalms challenge and augment the prevailing presentation of silence in the Psalter's hymnic passages, where verbal terminology dominates (e.g., 145:21) and silence signals the absence of praise (e.g., Ps 30:10, 13). Though silence functions differently in Psalms 19 and 65, both psalms involve a constructive interplay of silence and praise, and both contextualize this interplay with explorations of human sin and nonhuman creation. Ultimately, these texts illustrate the marginal, differentiated, and yet integral presence of silence, beyond its communication of the absence of God, as part of the psalmic dialogue of praise.
Keywords: Psalm 19; Psalm 65; Creation; Hymn; Lament; Praise; Psalms; Silence; Sin